Is childhood asthma still underdiagnosed and undertreated in Istanbul? - (:unkn) unknown (BLACKWELL PUBLISHING, 2007)
Background: Childhood asthma is reported to be underdiagnosed and undertreated worldwide. The purpose of the present study was to investigate the rate of underdiagnosis and undertreatment among children diagnosed with asthma in a tertiary reference center in Turkey. Methods: A questionnaire survey was carried out among the parents of 1134 patients diagnosed with asthma in a tertiary reference outpatient clinic. Results: Mean age of the patients was 4.9 years (range 1-17 years). Of these children 45.5% had recurrent asthma attacks (average 4.8 attacks per year) and 24.7% had only the symptom of vigorous fits of coughing. Although they had been symptomatic for 29.6 months, only 41.1% were diagnosed as having asthma before admission to the clinic. In this study group 61.3% had received some form of asthma treatment, but only 21.1% of all patients were treated according to the guidelines. The rate of treatment according to guidelines was lower in the children under 6 years of age than older children (18.8 vs 24.2%, respectively, P = 0.02). Conclusions: Underdiagnosis and undertreatment of childhood asthma still seem to be a major problem in the management of childhood asthma, especially in preschool children, even after the recommendations of guidelines.
Keywords: asthma; children; underdiagnosis; undertreatment; DOCTOR DIAGNOSED ASTHMA; RESPIRATORY SYMPTOMS; ALLERGIC DISEASES; PRESCHOOL-CHILDREN; RISK-FACTORS; PREVALENCE; TURKEY; ENVIRONMENT; SENSITIZATION; ADOLESCENCE